Religious Practices on HIV/AIDS Patients - Andrianto, Muhammad Bagus; Padila, Padila; Andri, Juli; Sartika, Andry; J, Harsismanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the relationship between religious practices of people living with HIV/AIDS. The design in this study is a descriptive-analytic study. The survey results from 153 respondents that most of the religious practices of Islam in the HIV/AIDS group were moderate 105 (68.6%). In conclusion, there is a significant relationship between the level of spiritual practice of people living with HIV/AIDS. Keywords: HIV/AIDS, Religious Practice